Objective Dimensions on Fishermen's Quality of Life - Laratmase, Antonia Junianty; Rahmani, Sofia Fitri; Wahyuari, Wahyuari (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2023)
The purpose of this study was to find out fishermen’s quality of life construct validity used survey by involving 44 fishermen in Cimalaya, Karawang. Data analyzed by correlations test, cronbach’s alpha and factor analysis (CFA). The Study results revealed that there were four objective dimensions of fishermen’s quality of life that can be seen from the indicators: (1) income with value of 0.455; (2) Marital status with value of 0.545; (3) Health status with value of 0.691; and (4) Social relationship with value of 0.638. Those values were good since they were above 0.4 or had little tolerance to above 0.25. For this reason, the objective dimensions of quality of life can be measured in terms of harmony and ability which is the integration of quality of life.